Genetic Divergence in Taramira (Eruca sativa Mill.) - M.L. Jakhar,; R.N. Jajoria,; K.C. Sharma,; Shyoji Ram, (Journal of Oilseed Brassica, 2026)
One hundred and fifty genotypes of taramira (Eruca sativa Mill.) were evaluated to estimate geneticdivergence for seed yield and its component characters. All the genotypes and check varieties were groupedin to 10 clusters. Cluster composition indicated that geographic diversity was not related to genetic diversity.Among all the characters, plant height contributed the most towards total D2 followed by number of siliquaeper plant and number of seed per siliqua. Cluster 10 had highest mean value for seed yield per plant andnumber of secondary branches per plant while cluster VII had highest mean value for number of siliquae perplant. On the basis of D2 analysis, nine genetically diverse cluster pairs, 12 genetically diverse and superiorgenotypes were identified